Pendampingan Pastoral Konseling kepada Orang Tua yang Memiliki Anak Penyandang Disabilitas dengan Pendekatan Clien – Centered - Ronald Patiar Hutabarat; Rencan Carisma Marbun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Basically, God created His creatures perfectly. On the other hand, it turns out that God also created humans who do not have five senses, or incomplete body functions, such as the blind, deaf, physically disabled, even mentally disabled so that they have limitations in carrying out daily activities and are often considered different from others. A person who has physical or mental limitations due to illness or injury is called a disability. Being a person with a disability not only affects the person themselves, but often their families, especially their parents. The purpose of this study was to determine the application of pastoral care for parents who have children with disabilities. This study uses a qualitative descriptive method. The population and sample of this study were parents, namely the father and mother of a child with disabilities in Pamalian village, Sorkam sub-district, Central Tapanuli district. In an effort to provide pastoral counseling assistance with a Client Centered approach to parents who have children with disabilities, there are several approaches taken by the companion, namely, listening, reflecting, explaining, and being fully present. From the research results, pastoral counseling with a client-centered approach can help parents who have children with disabilities understand that what happened to their child is not a mistake or punishment due to sin so that parents can accept their child's condition.